Empowerment and Accountability and Multi-layered Contexts of Influences: Parenting and the Avoidance of Harm in Harare, Zimbabwe - Dari, Noreen Kudzanai Wini; Mawodza, Obdiah; Olson, Ericka Mingo, Bradley D. (Wiley-Blackwell Publishing Ltd, 2021)
In this paper, the authors discuss multi-level systems for parenting in Harare, Zimbabwe. At the micro-system level, the Tirere Pamwe parenting program is a supportive, empowering prototype, designed to educate parents on child development, with a special focus on socio-emotional development, from birth to age 18 years. The program has been delivered to a diverse group of parents, in diverse settings, which has helped to bring a greater contextual relevance to parenting practices, and seems thereby to have increased the mental well-being of children. At the macro-system level, international law and Zimbabwaean laws emphasise the need to protect children from both physical and psychological harm. These different layers are examined through the varying theoretical perspectives of community psychologist Julian Rappaport (1977, 1981, 1987, 2000, 2005), such as his emphasis on paradox, empowerment, second-order change, and narrative.